The Enjoyment as Strategy for the Construction of the Post-AIDS Body - García Sangrador, Raúl (2017)
The present article studies the experience and the aesthetic production resulting from the disease, starting from the definitions of pleasure and enjoyment of Roland Barthes; the neo-baroque of Severo Sarduy; the eroticism of Georges Bataille, and the celebration or carnival, by Mijail Bajtin. For this, an analysis of the erotica of the disease is carried out from two case studies (Robert Gober and Raúl García Sangrador), where art uses the AIDS phenomenon to create new meanings of the current corporality. It is concluded that, from enjoyment, it is possible to define the erotic of the disease as a challenge for the understanding of current art and a space of tension where AIDS becomes an artistic-political phenomenon.